2024 re-emergence of coxsackievirus A24 variant causing an outbreak of acute hemorrhagic conjunctivitis in the South West Indian Ocean - Audrey Mirand; Maxime Bisseux; Louis Collet; Vincent Lacoste; Violaine Pierres; Jonhson Raharinantoanina; Richter Razafindratsimandresy; Hélène Chabrolles; Jean-Luc Bailly; Maël Bessaud; Anabelle Lapostolle; Cécile Henquell (Emerging Microbes and Infections)
In early 2024, an outbreak of acute hemorrhagic conjunctivitis occurred in Mayotte and in Madagascar, two islands in the Indian Ocean. Real-time diagnosis and genotyping identified a different lineage of coxsackievirus A24 variant (CVA24v) from the current Asian outbreak. Although no recombination event had been detected in all previously reported CVA24v-associated outbreaks associated with the subgenotype IV, we characterized a putative recombinant strain by full-length genome sequencing.